Medial meniscus extrusion is directly correlated with medial tibial osteophyte in patients received reconstruction surgery for anterior cruciate ligament injury: A longitudinal study. Issue 4 (December 2022) - Hada, Shinnosuke; Kaneko, Haruka; Liu, Lizu; Aoki, Takako; Takamura, Tomohiro; Kinoshita, Mayuko; Arita, Hitoshi; Shiozawa, Jun; Negishi, Yoshifumi; Momoeda, Masahiro; Kubota, Mitsuaki; Aoki, Shigeki; et al.
Abstract: Objective: Anterior cruciate ligament (ACL) injury is one of the causes for post-traumatic knee osteoarthritis (OA), and ACL reconstruction surgery is reportedly unable to prevent OA development. In early-stage knee OA, medial meniscus extrusion (MME) is closely correlated with tibial medial osteophyte width, which consists of bone and cartilage -parts. However, the relationship between MME and osteophyte in ACL-injured patients remains elusive. We examined MME and osteophyte and their relationship in ACL-injured patients before and after surgery. Design: Thirty ACL-injured patients who underwent surgery (30.7 years old, on average) were enrolled. Correlations between magnetic resonance imaging (MRI)-detected OA changes and MME before and after surgery (7.6 months interval) were analyzed. Results: MME (>3 ​mm) was present in 16.7% and 26.7% of the patients before and after surgery, respectively, and MME was significantly increased after surgery (2.4 ​± ​1.3 ​mm) than before surgery (1.9 ​± ​1.2 ​mm) ( p ​< ​0.0001). Full-length tibial osteophyte width measured by T2 mapping MRI was significantly increased after surgery (1.9 ​± ​0.7 ​mm) than before surgery (1.4 ​± ​0.6 ​mm) ( p ​< ​0.0001). Among OA structural changes, only medial tibial osteophyte width directly correlated with MME before surgery (β ​= ​0.962) ( p ​< ​0.001) and after surgery (β ​= ​0.928) ( p ​= ​0.001). All the patients with MME had medial tibial osteophyte before and after surgery. A direct correlation was observed between changes of MME and those of medial tibial osteophyte width before and after surgery (r ​= ​0.63) ( p ​< ​0.0001). Conclusion: MME and medial tibial osteophyte were simultaneously increased after surgery. In addition to close correlation between MME and medial tibial osteophyte width, changes of MME and medial tibial osteophyte width before and after surgery were directly correlated.